The last juror - Grisham, John (London : Arrow Books, 2004)
In 1970, one of Mississippi's more colorful weekly newspapers went bankrupt. To the surprise and dismay of many, ownership was assumed by a 23 year-old college dropout, named Willie Traynor. The future of the paper looked grim until a young mother was brutally raped and murdered by a member of the notorious Padgitt family. Willie Traynor reported all the gruesome details and the paper began to prosper. The murderer, Danny Padgitt was tried before a packed courthouse in Clanton, Mississippi. The trial came to a startling and dramatic end when he was found guilty. He was sentenced to life in prison, but in Mississippi, in 1970,'life' didn't necessarily mean'life' and nine years later Danny Padgitt managed to get himself paroled. He returned to Ford County and the retribution began.
Koleksi sumbangan Dr Mohamad Nasrin Mohamad Nasir
Keywords: Trials (Murder) -- Fiction; Newspaper publishing -- Fiction; Ex-convicts -- fiction; Jury -- Fiction